2018
DOI: 10.3390/en11081933
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Matching and Instantaneous Power Allocation for the Hybrid Energy Storage System of Pure Electric Vehicles

Abstract: In order to complete the reasonable parameter matching of the pure electric vehicle (PEV) with a hybrid energy storage system (HESS) consisting of a battery pack and an ultra-capacitor pack, the impact of the selection of the economic index and the control strategy on the parameters matching cannot be ignored. This paper applies a more comprehensive total cost of ownership (TCO) of HESS as the optimal target and proposes an optimal methodology integrating parameters and control strategy for the PEV with HESS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Therefore, the statistical conclusion shows that bond-breaking and atomic size effects are independent and substantial contributors to GB cohesion. To quantitatively explore the relative significance of each input variable for improving the prediction performance, the mean impact value (MIV) analysis was conducted using the similar method previously by Jiang et al [50] and Liu et al [51]. The MIV values for each input variable on each output variable are calculated and shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the statistical conclusion shows that bond-breaking and atomic size effects are independent and substantial contributors to GB cohesion. To quantitatively explore the relative significance of each input variable for improving the prediction performance, the mean impact value (MIV) analysis was conducted using the similar method previously by Jiang et al [50] and Liu et al [51]. The MIV values for each input variable on each output variable are calculated and shown in Figure 5.…”
Section: Methodsmentioning
confidence: 99%
“…The performance requirement-indicator correlation matrix R is obtained by equation 12- (13). And the final weight coefficient of vehicle performance indicator v f is obtained by equation (14). After calculation and analysis, the final obtained HOQM of R-EEV based on market requirements is shown in Figure 4.…”
Section: Determination Of the Weight Coefficient Of Vehicle Technicalmentioning
confidence: 99%
“…The other focus is the optimization and analysis of vehicle performance indicators under a multi-objective. XY Jiang et al 14 carried out a multi-objective optimization (MOO) research on semi-active battery/supercapacitor energy storage system of electric vehicle. Q Zhu et al 15 used Advisor and Matlab simulation to simulate and analyze the powertrain of R-EEV.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the optimization results can be applied to multiple operating conditions and improve the vehicle fuel economy. Jiang et al [23] proposed an optimal methodology integrating system parameters and control strategies for pure electric vehicles (PEVs) with a hybrid energy storage system. This approach significantly improved the vehicle economy in urban and suburban conditions.…”
Section: Introductionmentioning
confidence: 99%